Strategi Pembelajaran Guru Dalam Meningkatkan Motivasi Belajar Siswa Melalui Mata Pelajaran PPKn di SMA Advent Waropen Papua - Woisiri, Carolina Justevani; Biringan, Julien (Tumoutou Social Science Journal, 2025)
This study aims to describe various strategies used by teachers in an effort to increase students' learning motivation in the subject of Pancasila and Citizenship Education (PPKn) at Waropen Adventist High School, Papua. The background of this study is the problem of low student enthusiasm for learning subjects PPKn. This can be seen from the lack of student involvement in the learning process, delay in completing assignments, and the achievement of learning outcomes that are still below expectations. The approach used in this study is a qualitative approach with a descriptive method. Data was collected through interviews, direct observations in the classroom, and documentation review. The findings in this study reveal that PPKn teachers at Waropen Adventist High School apply learning strategies that are tailored to the characteristics of students. Some of the methods used include group discussions, simulations, the use of visual media, as well as problem-based learning approaches and debates. In addition, teachers also play a role as encouragers by creating a fun and communicative learning atmosphere, giving rewards, and approaching students personally. These strategies have been proven to have a positive effect on increasing learning motivation, student participation in learning, and their understanding of the material taught in PPKn lessons.